The role of customary institutions and the challenges they are facing in transforming violent conflicts: the case of the Konso and Ale ethnic groups in southern Ethiopia - Mulumebet Major; Fekadu Beyene; Gutema Imana; Dereje Tadesse; Tompson Makahamadze (Cogent Social Sciences)
Several interethnic violent conflicts have escalated in Ethiopia over the last few years. Particularly in the southern regional state of Ethiopia, the conflict between the Konso and Ale ethnic groups has its roots in intercommunal crises. This study examines the role of customary institutions (CIs) in the transformation of violent conflict between the Konso and Ale ethnic groups in southern Ethiopia. The study employed a case-study research design with a qualitative approach. The data are organised and analysed thematically. The 1991 federalism and the autonomy of ethnic groups led to conflicts between the two communities. The study reveals that prior to the 1991 Ethiopian regime, the Konso and Ale ethnic groups had robust CIs used to transform conflicts ranging from personal to criminal issues. However, currently, CIs have not been able to end the ongoing conflict due to sociopolitical factors like the complex nature of conflict, erosion of traditional values due to modernization, government interventions, youth and religious misunderstandings of CIs, and the limited authority of customary systems. The new state structure and formal institutions that have replaced traditional ones with politically motivated institutions have also reduced the significance of the system.